The Burden of New Leprosy Cases in India: A Population-Based Survey in Two States. (20th March 2013) - Kumar, Anil; Husain, Sajid
Abstract : Objectives . To assess the burden of new leprosy cases in India and the efficiency of case detection work by ASHA in general health system. Methods . A sample survey of 804, 536 persons was undertaken in 8 districts during 2009-2010: 4 each in Haryana (low endemic for leprosy) and Uttar Pradesh (high endemic for leprosy). About 20% population was covered from urban areas. Results . The survey suggested that burden of new case detection rate of leprosy in India per 10, 000 population could be 4.41 in comparison to 1.09 as per government records. When present observation is adjusted to team performance in rural area, the NCDR increased to 10.64 per 10, 000. This leads to suggest that NCDR in India could further increase to 9.76 times when adjusted to team performance. This data suggest that large numbers of early leprosy cases do not reach the health facilities where leprosy treatment is provided, although some chronically ill patients reach late, and thus multibacillary disease is found more in passive reporting. This could also be an indicator of a large number of established cases not being sufficiently self-motivated or lacking knowledge to utilize the free diagnosis and treatment services. Thus, the programme needs to be designed to meet these objectives effectively to better utilize the available services to reduce the leprosy burden. Conclusion . Active survey detected many folds higher leprosy cases in community, and this suggests that the information, education, and communication based approaches have a very minimal effect. If the programme continues to be based on IEC activities, the information should be designed in such a way that most persons suspected to have leprosy can know about free treatment, place of availability, and its effectiveness. However, leprosy elimination campaign surveys may be used as a tool to filter large pool of cases from community.